The neural mechanisms underlying the processing of consonant, vowel and tone during Chinese typing: an fNIRS study - Yu, Jianan; Zou, Yun; Wu, Yan (Frontiers in Neuroscience, 2023)
Many studies have explored the role of consonant, vowel, and tone in Chinese word identification or sentence comprehension. However, few studies have explored their roles and neural basis during Chinese word production, especially when involving neural basis. The present fNIRS study investigated the neural mechanisms of consonant, vowel, and tone processing during Chinese typing. Participants were asked to name the Chinese characters displayed on a computer screen by typing on a keyboard while hearing a simultaneously presented auditory stimulus. The auditory stimulus was either consistent with the characters’ pronunciation (consistent condition) or mismatched in the consonant, vowel, or tone of the character pronunciation. The fNIRS results showed that compared with the consistent condition (as baseline), the consonant mismatch condition evoked lower levels of oxygenated hemoglobin (HbO) activation in the left inferior frontal gyrus Broca’s triangle and left superior temporal gyrus. Vowel mismatch condition evoked a higher level of HbO activation in the top of the left inferior frontal gyrus and left middle frontal gyrus. The regions and patterns of brain activation evoked by tone mismatch were the same as those of vowel mismatch. The study indicated that consonant, vowel and tone all play a role in Chinese character production. The sensitive brain areas were all in the left hemisphere. However, the neural mechanism of consonant processing differed from vowel processing in both brain regions and patterns, while tone and vowel processing shared the same regions.